Real-time quantification and source apportionment of fine particulate matter including organics and elements in Delhi during summertime. (15th September 2021) - Shukla, Ashutosh K.; Lalchandani, Vipul; Bhattu, Deepika; Dave, Jay S.; Rai, Pragati; Thamban, Navaneeth M.; Mishra, Suneeti; Gaddamidi, Sreenivas; Tripathi, Nidhi; Vats, Pawan; Rastogi, Neeraj; Sahu, Lokesh; et al.
Abstract: Delhi is one of the most polluted cities globally, with frequent severe air pollution episodes and haze events occurring in recent years, thereby compelling us to understand the sources to develop effective mitigation plans. Complete chemical characterization of fine particulate matter (PM2.5 ) components (non-refractory, refractory and elements) with high time resolution has been done during the summer season (June–July 2019). The total PM equivalent (PM2.5(eq) ) was 28.7 ± 13.2 μg m −3 of which elements dominated the PM2.5(eq) with 34% contribution followed by organics (28%), black carbon (BC) (17%), SO4 2− (10%), Cl − (5%) NH4 + (3.5%) and NO3 − (2.5%). The contributions from organic aerosols (OA) and SO4 2− were observed to be more than Cl − and NO3 − . The total elemental mass concentration (PMEl ) was mostly contributed (~96%) by Si, S, Cl, Ca, K, Fe and Al with Si and S alone contributing around 50% of PMEl . Crustal elements (Al, Fe, Ca and Si) were highly enhanced in summer than elements emitted from anthropogenic emissions (Cl, S, K, Pb and Zn). Source apportionment (SA) of PM was performed using positive matrix factorization (PMF) together with ME-2 (multilinear engine) for OA and elements, separately. PMF on both datasets helped resolve sources such as combustion, industrial, dust-related, incineration and traffic. OA PMF identified three factors related to primary emissions: hydrocarbon-like OA (HOA, 12.3%), solid fuel combustion (SFC, 16.2%) and cooking OA (COA, 7.3%) and two oxygenated OA (OOA): semi-volatile OOA (SVOOA, 15.2%) and low-volatile OOA (LVOOA, 49.1%). The elemental PMF resolved 8 factors: dust (52.5%), S-rich (16.2%), Cl-rich (10.7%), 2 SFC factors (10.5%), non-exhaust (7.2%), Cu-rich (1.5%) and industrial (1.4%). The contribution of BC to total PM mass is shown to increase in the summer compared to previous studies reported for the winter season. The secondary oxidized sources dominated both the OA and elements SA during the summer with 64.3% and 27% (dust not considered) contribution, respectively. The domination of secondary sources implies that it is crucial to control the secondary aerosols' precursors in Delhi for developing pollution control strategies. The ME-2 resolved factors, coupled with concentration weighted trajectory (CWT) showed the probable major elemental source regions of local origin (Delhi- National Capital Region (Delhi-NCR)) as well as regional (from Punjab, Haryana, Uttar Pradesh and Pakistan). The local sources included Cu-rich (Haryana) and SFC-II (Delhi and Uttar Pradesh), while the regional sources were dust (south-west (SW)), industrial, Cl-rich (north-west (NW)), SFC-I (east and south-east (SE)) and S-rich (SE). Graphical abstract: Image 1 Highlights: First time complete characterization of PM2.5 (non-refractory, refractory and elements) during summer in Delhi. Source apportionment of highly time-resolved organics and elements from real time instruments. Distinct sources are resolved in Delhi during summer along with their potential regions of origin. Dust storms and Cl episodes have been captured using high time-resolution AMS and Xact data. Secondary oxidized sources dominate the summertime than primary (anthropogenic) sources.